Review of Factors Influencing Efficient Utilization of Fly-overs and Express Roads in Africa - Godfrey Alinaitwe; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
The efficient utilization of fly-overs and express roads in Africa is pivotal for enhancing transportation networks, alleviating congestion, and driving economic development. This review paper examines the factors influencing the utilization of these infrastructures across the continent from 2010 to 2024. By synthesizing findings from various empirical studies, the paper identifies key factors such as economic conditions, urbanization, policy frameworks, and technological advancements that impact the effectiveness of fly-overs and express roads. The study reveals that suboptimal design, inadequate maintenance, economic constraints, and governance issues are major challenges faced by many African countries. These factors often lead to underutilized infrastructures, which do not fully meet the needs of the population. The paper highlights the importance of addressing these challenges through comprehensive urban planning, policy development, and technological integration. Recommendations include enhancing economic stability, strengthening governance, improving urban planning strategies, and investing in smart transportation technologies. The study provides valuable insights for policymakers and stakeholders to improve infrastructure projects and contribute to sustainable economic growth in Africa. Future research should delve into case studies and the impact of emerging technologies on infrastructure efficiency to offer more nuanced perspectives. The findings contribute to the broader discourse on infrastructure management and urban planning, emphasizing the need for coordinated efforts to optimize the utilization of fly-overs and express roads.